Social and Familial Factors in the Course of Bipolar Disorder: Basic Processes and Relevant Interventions. - Miklowitz, D; Johnson, S (2009)
This article reviews the role of social factors, notably life events and family relationships, in the course of bipolar illness in adults and youth. We also discuss psychological variables that help explain the vulnerability of bipolar patients to social environments, including personality factors (e.g., neuroticism), reward sensitivity, and difficulty with the accurate perception of facial emotions. Bipolar patients are highly sensitive to reward, and excessive goal pursuit after goal-attainment events may be one pathway to mania. Negative life events predict depressive symptoms, as do levels of familial expressed emotion. Psychosocial interventions can speed recoveries from episodes and delay recurrences over 1-2 year intervals. Future research should examine the nature of vulnerability/stress interactions at different phases of development, and the role of psychosocial interventions in altering these processes.